PENGARUH KINERJA LINGKUNGAN, SENSITIVITAS INDUSTRI, DAN UKURAN PERUSAHAAN, TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DI PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tanti Kustina (Fakultas Ekonomi, Program Studi Akuntansi, Universitas Warmadewa, 2020)
Corporate Social Responsibility is a disclosed transparently and is expected to obtain legitimacy from the public. This study aims to determine the effect of Environmental Performance, Company Size, and Industry Sensitivity on the disclosure of Corporate Social Responsibility in Manufacturing Companies listed on the Indonesia Stock Exchange in 2015 - 2017. The technique of sample selection uses purposive sampling in 24 manufacturing companies. Data analysis techniques used in this study are the classic assumption test and multiple linear regression test. All variables are stated to be free from interference from classical assumptions. From the results of multiple linear regression test results f test obtained a significant value of 0,000 or <0.05. This means that Environmental Performance, Company Size, and Industrial Sensitivity in Manufacturing Companies listed on the Indonesia Stock Exchange have a significant simultaneous effect. Partial testing shows the results that the variable Environmental Performance and Industrial Sensitivity has a positive and significant effect on Corporate Social Responsibility while the Company Size variable has a negative influence on Corporate Social Responsibility.